1977
DOI: 10.1139/z77-008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of bovine growth hormone on growth rate, appetite, and food conversion of yearling coho salmon (Oncorhynchus kisutch) fed two diets of different composition

Abstract: Paired groups of yearling coho salmon at 10 °C and on a natural photoperiod were fed twice daily either Oregon moist pellets (OMP) or a diet with poultry offal (PO) as the main protein source. The fish were fed either 0.8% body weight per day (dry weight of food (g)/wet weight of fish (g)) or to satiation. Coho in one of the groups for each diet–ration combination received, by intramuscular injection, 10 μg (0.0092 IU) of bovine growth hormone (bGH) per gram body weight one time per week for 56 days. Those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 33 publications
3
37
0
Order By: Relevance
“…In fish, it is well established that administration of exogenous GH increases food intake and feeding behavior (Johnsson and Bjornsson, 1994;Markert et al, 1977). Similarly, elevated GH in transgenic salmon induced heightened feeding motivation, increased food intake and feeding behavior (Abrahams and Sutterlin, 1999;Devlin et al, 1999;Sundstrom et al, 2003).…”
Section: Gh Increased Food Intakementioning
confidence: 99%
“…In fish, it is well established that administration of exogenous GH increases food intake and feeding behavior (Johnsson and Bjornsson, 1994;Markert et al, 1977). Similarly, elevated GH in transgenic salmon induced heightened feeding motivation, increased food intake and feeding behavior (Abrahams and Sutterlin, 1999;Devlin et al, 1999;Sundstrom et al, 2003).…”
Section: Gh Increased Food Intakementioning
confidence: 99%
“…The increase in weight associated with growth in fish appears to be due to a combination of increased appetite [14, 15] and increased feed conversion [[14, 16, 17]; for review,see [18]]. In fish, both GH administration [19, 20] and GH transgenesis [21] result in increased growth that might be attributed to increased feeding and improved food assimilation [20, 22].…”
Section: Gh Regulation Of Growth and Metabolismmentioning
confidence: 99%
“…In addition to SRIF, noradrenaline and serotonin have been shown to act inhibitory on GH release. Stimulatory action on GH secretion, on the other hand, has been demonstrated by everal factors including growth-hormone releasing hormone (GHRH), dopamine (DA), neuropeptide Y (NPY), gonadotropin-releasing hormones (GnRHs), thyrotropin-releasing hormone (TRH), cholecystokinin (CCK), bombesin and activin 4,5) Using different treatment protocols and GH of both heterologous and homologous origin, it has been shown that GH increases specific growth rates in length and weight in a variety of teleost species 14,1 ,16,1,7) Similarly , in several fish species, germline GH-transgenic strains exhibit enhanced growth rates compared with non-transgenic strains18,19,20,21) The increase in weight has been suggested to be caused by a GH-induced increase in appetite 22,23,24), and/or in creased feed conversion efficiency22, 25,26) Although some data indicate a positive correlation between specific growth rate and plasma GH levels 27, there seems to be no general relationship between growth rate and circulating GH levels in fish28,29. There may be multiple reasons for this.…”
mentioning
confidence: 99%
“…The GH-induced increase of growth in fish is usually accompanied by a decrease in condition factor, indicating that the fish become relatively leaner dur ing GH treatment 34,35,22,25) This is most likely due to the strong stimulatory effect of GH on length growth, even during periods of starvation24), in combination with its effects on metabolism.…”
mentioning
confidence: 99%